137k views
5 votes
2x - 1y = -9

y = -5 - 5x

please explain the answer and not just tell me the answer?

1 Answer

4 votes
X=-2 y=5

Explanation: your first step would be substitute the equation (y=-5x-5 in for the y in the other equation 2x-1y=-9 making it 2x-1(-5x-5)=-9 then do the distributive property to get 2x+5x+5=-9 then combine like terms and get 7x+5=-9 then you subtract 5 from -9 and get -14 then you get 7x=-14 then get a final answer of x=-2. Then plug in x=-2 to your first equation y=-5(-2)-5 and then you get 10 -5 and get y=5
User Erich Gubler
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.